Silage maize quality in different uses of Italian ryegrass and soil management methods after liming. Issue 2 (28th January 2018) - Alves dos Santos, Jéssica; da Fonseca, Adriel Ferreira; Barth, Gabriel; Zardo Filho, Renato
ABSTRACT: The effects of lime application with multiple soil management methods and uses on dry matter (DM) yield and crude protein (CP) content of Silage maize cropping in succession with Italian ryegrass (ryegrass) from 2009 to 2014 in a southern Brazilian Oxisol were studied. The experimental design was completely randomized block in split-plot with four replications. The main plot treatments were the four soil management methods: conventional tillage (CT), minimum tillage (MT), no-tillage (NT) and chiseled no-tillage (CNT). The sub-plots treatments were the three uses of Italian ryegrass (ryegrass): cover crop (CC), silage (S), and grazing dairy heifers as part of integrated crop-livestock system (ICL). In all the years, the maize was sown approximately 30 days after the ryegrass desiccation with herbicide. In the medium-term (5 yrs.) after liming, soil management methods did not change DM yield and CP content in silage maize. The use of ryegrass for S and ICL did not change DM yield, but notably maintained or increased CP content in silage maize after liming. The use of ryegrass only as CC provided less measurable benefits than the combined production system of silage maize with ryegrass.